CONTROL DIFFUSION PROCESSES WITH LIPSCHITZ CONTINUITY OF DRIFTS - Komang Dharmawan (Jurnal Matematika, 2012)
Control diffusion processes has been found in a wide field of applicationsas in stochastic optimal control and in mathematical finance via the theory ofhedging and nonlinear pricing theory for imperfect markets. In this paper we discussthe control diffusion process with time and space dependent coefficients and localLipschitz continuity of the drift. The results show that the controlled process Xs;;utis independent of control u for a constant.